2018
DOI: 10.37358/rc.18.11.6741
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Way to Detect Cardiovascular Risk

Abstract: Cardiovascular risk means the degree of risk for atherosclerotic cardiovascular pathology, predictable by quantifying the risk factors (RF) existing in each individual. Global cardio-metabolic risk is the overall risk of developing type 2 diabetes mellitus (T2DM) and/or CVD, including myocardial infarction (MI) and stroke, which is due to a bundle of risk factors. The cardio-metabolic risk is based on the concept of continuous risk. The importance of cardiovascular / cardio-metabolic risk is particular because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…For the immune-phenotype with both receptors negative, ER-/PR-we had 24 cases (24%). The results were comparable to those obtained in similar studies that concluded that almost 50% of invasive mammary carcinomas have both receptors positive whilst 25% are lacking in them [8][9][10][11][12]. The ER+/PR-phenotype represents a distinct group because it usually is accompanied by high clinical and biological aggressiveness and have the least satisfactory response to hormone therapy in comparison to other phenotypes [13][14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…For the immune-phenotype with both receptors negative, ER-/PR-we had 24 cases (24%). The results were comparable to those obtained in similar studies that concluded that almost 50% of invasive mammary carcinomas have both receptors positive whilst 25% are lacking in them [8][9][10][11][12]. The ER+/PR-phenotype represents a distinct group because it usually is accompanied by high clinical and biological aggressiveness and have the least satisfactory response to hormone therapy in comparison to other phenotypes [13][14][15][16].…”
Section: Resultssupporting
confidence: 83%
“…DM and deprivation is, no doubt, a twin problem in Arad County. The association between DM and HTN with depression has been well known for at least three decades [24,25,26,27]. DM and HTN frequently occur together; there is substantial overlap between diabetes and hypertension in etiology and disease mechanisms because obesity, inflammation, oxidative stress, and insulin resistance are thought to be the common pathways [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The path of clinician thinking may be experiencing multiple traps, and relying on stereotypes, past experiences, is and can be extremely damaging [19][20][21][22][23][24][25][26].…”
Section: Fig 4 Karyotypementioning
confidence: 99%